2017
DOI: 10.15604/ejef.2017.05.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Human Capital and Economic Growth: An Application to Developing Countries

Abstract: High and sustainable economic growth, that is an important indicator of life quality, is an essential condition in the realization of economic growth. In this regard, achieving strong economic growth in developing countries which mostly need development today, is one of the most debated topics. For many years, physical capital has been recognized as the most important determinant of economic growth. New approaches to economic growth have been developed since 1980s. In this context, according to endogenous grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
7
0
2
Order By: Relevance
“…Notably, we observe that the role of labour for economic progress varies with the level of income and regions. Previous literature has also confirmed similar findings regarding human capital and economic growth (Abbas & Foreman-peck, 2008;Abimbola & Abdulfatai, 2017;Altiner & Toktas, 2017;Amir, Khan, & Bilal, 2015;Khan, 2018).…”
Section: Laboursupporting
confidence: 72%
“…Notably, we observe that the role of labour for economic progress varies with the level of income and regions. Previous literature has also confirmed similar findings regarding human capital and economic growth (Abbas & Foreman-peck, 2008;Abimbola & Abdulfatai, 2017;Altiner & Toktas, 2017;Amir, Khan, & Bilal, 2015;Khan, 2018).…”
Section: Laboursupporting
confidence: 72%
“…Altiner and Toktas (2017) examined the impact of human capital development on the economic growth of selected 32 developing countries with a panel data analytical method. The study had two issues in focus: examining the direction of causality and the magnitude of the impact of the rise in the educational level on economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Findings showed that investments in primary and secondary education explained the variations to the growth of economic activities in East Asia better than the expenditures on tertiary and vocational education in South Asia. Altiner and Toktas (2017) examined the impact of human capital development on the economic growth of selected 32 developing countries with a panel data analytical method. The study had two issues in focus: examining the direction of causality and the magnitude of the impact of the rise in the educational level on economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The Human Capital Index is defined as a measure that describes the knowledge, information, ideas, and expertise of an individual, all of which can be obtained through formal education. Thus, several previous researchers proxied human capital using school enrollment rates (Altiner & Toktas, 2017;Barro, 2001;Hanushek, 2013;Mankiw et al, 1992;Murthy, 1997). The Human Capital Index in this study was formed using the method developed by the World Economic Forum ( 2017), which the authors further modify as follows.…”
Section: Operational Definition Of Variablesmentioning
confidence: 99%